ECOLOGY OF INDIAN ESTUARIES -XI.A PRELIMINARY SURVEY OF THE FISHERY RESOURCES OF THE ASHTAMUDI ESTUARINE SYSTEM - NAIR, N BALAKRISHNAN; KUMAR, K KRISHNA; NAIR, J RAJASEKHARAN; AZIS, P . K ABDUL; DHARMARAJ, K; ARUNACHALAM, M (Fishery Technology, 2017)
The fish fauna of the Ashtamudi, the second largest estuarine system in Kerala(8°53'-9°02' N Lat. and 76°31'--76°41 'E Long.) is listed. 97 species belonging to 39 families have been recorded, ofwhich69 are cornmerciallyimportant contributingto the fisheries of the Ashtamudi Estuary. Mullets, cichlids and the glassy perchlets are the most abundant groups and contribute appreciably to the landings. Results revealed that the estuarine system supports a good capture fishery which is seasonal. Majority of the fish fauna in the estuary are marine elements recruited from the adjoining Arabian Sea. An inventory of the craft and gear employed is presented and the sources of pollution in the estuarine system are described, aquacultural prospects of this area are discussed.